A Mutation in VWA1, Encoding von Willebrand Factor A Domain-Containing Protein 1, Is Associated With Hemifacial Microsomia - Wang, Yibei; Ping, Lu; Luan, Xiaodong; Chen, Yushan; Fan, Xinmiao; Li, Lianyan; Liu, Yaping; Wang, Pu; Zhang, Shuyang; Zhang, Bo; Chen, Xiaowei (Frontiers in Cell and Developmental Biology, 2020)
Background Hemifacial microsomia (HFM) is a type of rare congenital syndrome caused by developmental disorders of the first and second pharyngeal arches that occurs in one out of 5,600 live births. There are significant gaps in our knowledge of the pathogenic genes underlying this syndrome. Methods Whole exome sequencing (WES) was performed on five patients, one asymptomatic carrier, and two marry-in members of a five-generation pedigree. Structure of WARP (product of VWA1) was predicted using the Phyre2 web portal. In situ hybridization and vwa1-knockdown/knockout studies in zebrafish using morpholino and CRISPR/Cas9 techniques were performed. Cartilage staining and immunofluorescence were carried out. Results Through WES and a set of filtration, we identified a c.G905A:p.R302Q point mutation in a novel candidate pathogenic gene, VWA1. The Phyre2 web portal predicted alterations in secondary and tertiary structures of WARP, indicating changes in its function as well. Predictions of protein-to-protein interactions in five pathways related to craniofacial development revealed possible interactions with four proteins in the FGF pathway. Knockdown/knockout studies of the zebrafish revealed deformities of pharyngeal cartilage. A decrease of the proliferation of cranial neural crest cells (CNCCs) and alteration of the structure of pharyngeal chondrocytes were observed in the morphants as well. Conclusion Our data suggest that a mutation in VWA1 is functionally linked to HFM through suppression of CNCC proliferation and disruption of the organization of pharyngeal chondrocytes.